Effects of an Early Literacy Intervention for Linguistically Diverse Children: A Quasi-Experimental Study - Engel de Abreu, Pascale M. J.; Fricke, Silke; Wealer, Cyril (Frontiers in Psychology, 2020)
Phonological awareness and letter-sound knowledge underpin children's early literacy acquisition. Promoting these foundational skills in kindergarten should therefore lead to a better response to formal literacy instruction once started. The present study evaluated a 12-week early literacy intervention for linguistically diverse children who are learning to read in German. The study was set in Luxembourg where kindergarten education is in Luxembourgish and children learn to read in German in Grade 1 of primary school. One hundred and eighty-nine children (mean age = 5;8 years) were assigned to an early literacy intervention in Luxembourgish or to a business-as-usual control group. Trained teachers delivered the intervention to entire classes, four times a week, during the last year of kindergarten. The early literacy program included direct instruction in phonological awareness and letter-knowledge, while promoting print and book awareness and literacy engagement. Children were assessed pre-intervention, immediately post-intervention and at a nine-months delayed follow-up using measures in Luxembourgish and in German. At the end of the intervention, children in the intervention group performed significantly better than the control group on phonological awareness and letter-knowledge measures in Luxembourgish and the gains in phonological awareness were maintained at nine months follow-up. The effects generalized to measures of phonological awareness, word-level reading comprehension and spelling in German (effect sizes d > .25), but not to German word-level reading, at delayed follow-up. Intervention programs designed to support foundational literacy skills can be successfully implemented by regular teachers in a play-based kindergarten context. The findings suggest that early literacy intervention before school entry can produce educationally meaningful effects in linguistically diverse learners.